THE EFFECT OF FIBROTOLS ON THE PROPERTIES OF FINE-GRAINED CONCRETE (Web of Teachers: Inderscience Research, 2024)
The article presents the level of research, composition and properties of fiber-based concrete. The main direction for improving the properties of concrete is the use of fiber fibers as an additive to concrete.